Climate Change and Crop Production in Nigeria: An Error Correction Modelling Approach - Eregha, P. B.; Babatolu, J. S.; Akinnubi, R. T. (International Journal of Energy Economics and Policy, 2014)
Climate change is termed as one of the greatest challenges of the 21st century and this has posed threat to agricultural dependent economies. In fact report had it that developing economies are at disadvantage as they stand to experience some of the severe effects from climate change. It is against this backdrop that this paper examines the impact of climate change on crop production in Nigeria. Ten crops were selected and three climatic variables were used for the study. Data for the study were extracted from the Food and Agricultural Organisation database, World Development Indicator and the CBN Statistical Bulletin and the data covers the period 1970-2009. Analysis of data was done with cointegration approach. The study revealed that the effect of climatic variables on crop production varies depending on the type of crop and seasonal properties and length of days of the crop. In general, climate change effect was found to be pronounced on the output of the crops. It is therefore recommended that various adaptation strategies necessary for increased output of these crops be adopted by farmers and this can better be achieved with proper enlightenment programmes for the farmers. Keywords: climate change; global warming; crop production; error correction model JEL Classifications: Q54; Q56